Representativeness of single lidar stations for zonally averaged ozone profiles, their trends and attribution to proxies - Zerefos, Christos; Kapsomenakis, John; Eleftheratos, Kostas; Tourpali, Kleareti; Petropavlovskikh, Irina; Hubert, Daan; Godin-Beekmann, Sophie; Steinbrecht, Wolfgang; Frith, Stacey; Sofieva, Viktoria; Hassler, Birgit (Atmospheric Chemistry and Physics, 2018)
International audience This paper is focusing on the representativenessof single lidar stations for zonally averaged ozone profilevariations over the middle and upper stratosphere. From thelower to the upper stratosphere, ozone profiles from singleor grouped lidar stations correlate well with zonal meanscalculated from the Solar Backscatter Ultraviolet Radiome-ter (SBUV) satellite overpasses. The best representativenesswith significant correlation coefficients is found within15of latitude circles north or south of any lidar station. Thispaper also includes a multivariate linear regression (MLR)analysis on the relative importance of proxy time series forexplaining variations in the vertical ozone profiles. Stud-ied proxies represent variability due to influences outsideof the earth system (solar cycle) and within the earth sys-tem, i.e. dynamic processes (the Quasi Biennial Oscilla-tion, QBO; the Arctic Oscillation, AO; the Antarctic Os-cillation, AAO; the El Niño Southern Oscillation, ENSO),those due to volcanic aerosol (aerosol optical depth, AOD),tropopause height changes (including global warming) andthose influences due to anthropogenic contributions to at-mospheric chemistry (equivalent effective stratospheric chlo-rine, EESC). Ozone trends are estimated, with and with-out removal of proxies, from the total available 1980 to2015 SBUV record. Except for the chemistry related proxy(EESC) and its orthogonal function, the removal of the otherproxies does not alter the significance of the estimated long-term trends. At heights above 15 hPa an “inflection point”between 1997 and 1999 marks the end of significant nega-tive ozone trends, followed by a recent period between 1998and 2015 with positive ozone trends. At heights between 15and 40 hPa the pre-1998 negative ozone trends tend to be-come less significant as we move towards 2015, below whichthe lower stratosphere ozone decline continues in agreementwith findings of recent literature